2007
DOI: 10.3354/ame046225
|View full text |Cite
|
Sign up to set email alerts
|

Use of different phosphorus sources by the bloom-forming cyanobacteria Aphanizomenon flos-aquae and Nodularia spumigena

Abstract: A laboratory experiment was conducted to study differences in the use of varying phosphorus sources by the bloom-forming filamentous cyanobacteria Aphanizomenon flos-aquae and Nodularia spumigena. Axenic strains were grown in typical bloom-time light regimes under phosphate-replete, added organic phosphorus phosphate-depleted and completely phosphorus-depleted conditions. Responses to the treatments differed clearly. A. flos-aquae growth was dependent on an ample supply of inorganic dissolved phosphorus, where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
56
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(64 citation statements)
references
References 42 publications
6
56
2
Order By: Relevance
“…with respect to phosphorus (P) starvation and has a higher affinity for dissolved organic phosphorus (DOP), because of its lower substrate half-saturation constants (K M ) and the higher V max : K M ratio of the enzyme alkaline phosphatase (AP). These findings were confirmed by Vahtera et al (2007), who reported that under bloom conditions Nodularia is superior to Aphanizomenon in its ability to compete for phosphorus at low concentrations, more efficient in acquiring phosphate from organic sources, and better able to grow on intracellular phosphorus stores.…”
Section: Introductionsupporting
confidence: 61%
See 1 more Smart Citation
“…with respect to phosphorus (P) starvation and has a higher affinity for dissolved organic phosphorus (DOP), because of its lower substrate half-saturation constants (K M ) and the higher V max : K M ratio of the enzyme alkaline phosphatase (AP). These findings were confirmed by Vahtera et al (2007), who reported that under bloom conditions Nodularia is superior to Aphanizomenon in its ability to compete for phosphorus at low concentrations, more efficient in acquiring phosphate from organic sources, and better able to grow on intracellular phosphorus stores.…”
Section: Introductionsupporting
confidence: 61%
“…In fact, it is generally accepted that DOP is the main P source when DIP is exhausted (Nausch and Nausch, 2004;Vahtera, 2007). Accordingly, a high alkaline phosphatase activity (APA) indicates DOP utilisation (Cembella et al, 1984;Nausch, 1998;Hoppe, 2003) and may even be an indicator of P stress in cyanobacteria (Paasche and Erga, 1988;Wu et al, 2012).…”
Section: Dop As Phosphorus Sourcementioning
confidence: 99%
“…These observations, as well as the differences observed in the cellular nutrient content in this study, might show different requirements for each of these species, as well as differences in their efficiency for nutrient uptake. For instance, N. spumigena is a superior competitor at low phosphorus concentrations than A. flos-aquae, because it is more efficient at utilising organic sources and a better grower on intracellular stores [18]. This is in agreement with the high phosphorus content found in N. spumigena in comparison with those found in Anabaena sp.…”
Section: Resultssupporting
confidence: 77%
“…They are all common components of the phytoplankton community in the Baltic Sea and have the ability to reduce N 2 to NH 4 + , which can be very advantageous over other species, when other sources of inorganic nitrogen become unavailable [13]. The most abundant species in the yearly recurrent cyanobacterial blooms in the Baltic Sea are the non-toxic Aphanizomenon flos-aquae and the hepatotoxic Nodularia spumigena [18]. Anabaena sp., also hepatotoxic, is also present, but usually represents less than 10% of the total community cell numbers [4].…”
Section: Introductionmentioning
confidence: 99%
“…Resolving the life cycle allows variability in the seed population. Additionally, we implicitly assume that the phosphorus demand is covered through uptake of dissolved organic phosphorus and phosphorus storage (Huber and Hamel 1985;Vahtera et al 2007). …”
Section: Appendix B: Additional Sensitivity Experimentsmentioning
confidence: 99%